Blood-detected mitochondrial biomarker NSUN4: a potential indicator of ovarian aging - Jianheng Hao; Liying Liu; Boya Chang; Yuemeng Zhao; Yuanyuan Lai; Chunhui Tian; Huichao Xu; Haijun Wang; Laixi Ji; Jie Yang (Experimental Gerontology, 2025)
Background: Mitochondrial dysfunction is a key hallmark of aging, and blood-based biomarkers related to mitochondrial genes provide an effective means to assess ovarian aging progression. In this study, we aimed to explore the role of mitochondrial dysfunction-related genetic variations in determining the natural age at menopause (ANM) by applying both Mendelian randomization (MR) and summary data-based Mendelian randomization (SMR) approaches, complemented by experimental validation in animal models. Methods: Summary statistics on ANM, gene expression, DNA methylation, and protein abundance quantitative trait loci (eQTL, mQTL, pQTL) were obtained from public databases. Genetic variations associated with mitochondrial dysfunction were selected as instrumental variables, and SMR analysis was performed to investigate causal relationships with ANM. MR methods were also used to evaluate the causal effect of mitochondrial DNA copy number (mtDNA-CN) on ANM, with preliminary validation through animal experiments. Results: SMR and meta-analysis results identified NSUN4 as a critical regulator of ANM at both the gene expression and DNA methylation levels. A preliminary causal relationship between reduced mtDNA-CN and increased ANM risk was found, though further validation with larger datasets is needed. Animal experiments indicated that NSUN4 levels in blood reflect ovarian function decline and may correlate with its expression in ovarian tissue. Conclusions: The findings suggest that NUSN4 levels detected in the blood could serve as a potential biomarker for ovarian aging. This provides new insights into the role of mitochondrial dysfunction in reproductive age-related traits and may inform future targeted interventions to slow ovarian aging.